The Factors that Influence Student Motivation and Enthusiasm for Learning, Case Study at Nurul Huda Islamic Junior High School, West Java Indonesia - Halimah, Halimah; Juariah, Siti; Achmad, Listian Indriyani; Nenda, Nenda; Nugroho, Djoko; Ali, Saiful Mukti (DPPM Universitas Pelita Bangsa, 2023)
The purpose of this research is to find out the factors that can influence the motivation and enthusiasm of students to study at school. The study was conducted on students of Madrasah Tsanawiyyah Nurul Huda Tegal Gede. This research method uses a qualitative approach with interviews, observation and literature review. The research subjects were Grade 8 students with a total of 46 students. The results of the research show that the factors that influence student motivation and enthusiasm for learning are (1) there is someone that students like that they are trying to impress: 43.48%; (2) students actually want to gain knowledge: 34.78%; (3) students get pocket money if they go to school: 17.38%; and (4) students can play with their friends if they go to school: 4.35%. The analysis of the results of this study is: Allah created men and women to know each other and this influences the students’ motivation and enthusiasm for learning. Allah has regulated the etiquette of association with the opposite gender.